2019
DOI: 10.1177/1460458219833102
|View full text |Cite
|
Sign up to set email alerts
|

Automated classification of primary care patient safety incident report content and severity using supervised machine learning (ML) approaches

Abstract: Learning from patient safety incident reports is a vital part of improving healthcare. However, the volume of reports and their largely free-text nature poses a major analytic challenge. The objective of this study was to test the capability of autonomous classifying of free text within patient safety incident reports to determine incident type and the severity of harm outcome. Primary care patient safety incident reports (n=31333) previously expert-categorised by clinicians (training data) were processed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Several studies focused on classifying the type and severity of patient safety incident reports using data collected by different sources such as universities [ 75 ], and incident reporting systems such as Advanced Incident Management Systems (across Australia) and Riskman [ 67 , 75 , 76 ]. Others analyzed hospital clinical notes internally (manually annotated by clinicians and a quality committee) and data retrieved from patient safety organizations to identify adverse incidents such as delayed medication [ 68 ], fall risks [ 47 , 67 ], near misses, patient misidentification, spelling errors, and ambiguity in clinical notes [ 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies focused on classifying the type and severity of patient safety incident reports using data collected by different sources such as universities [ 75 ], and incident reporting systems such as Advanced Incident Management Systems (across Australia) and Riskman [ 67 , 75 , 76 ]. Others analyzed hospital clinical notes internally (manually annotated by clinicians and a quality committee) and data retrieved from patient safety organizations to identify adverse incidents such as delayed medication [ 68 ], fall risks [ 47 , 67 ], near misses, patient misidentification, spelling errors, and ambiguity in clinical notes [ 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, non-linear SVM uses the function to map the input vector to a high-dimension or infinite-dimension vector space and determines the hyperplane in the new space to classify the data points [ 30 ]. It has been previously observed that SVMs have consistently outperformed many other classifiers in text categorization problems, and they are less prone to the imbalanced data sets [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each free-text report was coded using the multi-axial PISA classification system, which is aligned to the World Health Organisation International Classification for Patient Safety, and has been extensively used to characterise patient safety incidents data in primary care [9][10][11][12][13].…”
Section: Data Codingmentioning
confidence: 99%